Analisis Dampak Kebijakan Tarif Pajak Resiprokal terhadap Ekspor Impor di Indonesia - Ahmad Rizki Ersa Dewantara; Elen Novia Apriliyanti; Nur Maya Karin; Nanda Putri Kholifatun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Reciprocal tariff changes imposed by the United States on its trading partner countries including Indonesia, create changes in export and import tariffs in Indonesia which result in a significant impact on the Indonesian economy, which has an impact on export and import sectors such as oil and gas, then non-oil and gas which includes processing industries, agriculture, forestry, fisheries, mining as well as consumer goods, raw / auxiliary materials, and capital goods. This research aims to analyze the impact of exports and imports in the country of Indonesia due to the reciprocal tax rate policy implemented by the United States. This research uses a qualitative approach with the type of content analysis, which involves collecting data from news articles, research reports, and relevant academic publications. The results showed that the imposition of reciprocal tariffs imposed by the United States against Indonesia caused an increase in imports from 2017 to 2020 by 1.38% in the consumer goods sector. On the other hand, the export side decreased in the oil and gas sector from 2017 to 2020 by 2.37% which resulted in disruption of economic stability in the global supply chain that created inflation, and increased imports in Indonesia resulted in competing local product prices with imported products so that many Indonesian manufacturing companies reduced production and terminated employment. From this research, it is expected that Indonesia will be able to maximize the opportunities that exist from the changes and challenges of global trade.